PERENCANAAN JARINGAN TRAYEK DAN RUTE ANGKUTAN PENGUMPAN (FEEDER) BUS TRANS METRO DEWATA DAN TRANS SARBAGITA DI KABUPATEN BADUNG - Suthanaya, Putu Alit; Saraswati, Ni Putu Delima Yogeswari; Wardani, Kadek (Program Studi Magister Teknik Sipil Universitas Udayana, 2026)
A feeder transport service is planned to support Bus Trans Metro Dewata and Trans Sarbagita in Badung Regency, specifically on the route from Mengwi Terminal to Pasar Adat Buduk, Mengwi Terminal to PT Indomarco Prismatama Tbk. Indomaret DC Mengwi Route, Mengwi Terminal to Sibang Gede Market Route, Mengwi Terminal to Monkey Forest Sangeh Route, Mengwi Terminal to Mambal Market Route, Mengwi Terminal to SMA N 1 Kuta Utara Route, Udayana University Rectorate to Jimbaran Beach Route, Bali State Polytechnic to Balangan Beach Route, Bali State Polytechnic to Pandawa Beach Route, ITDC Nusa Dua to Bali Tourism Polytechnic Route, ITDC Nusa Dua to Tanjung Benoa Beach Route, and ITDC Nusa Dua to Gunung Payung Beach Route. The methods used were demand potential analysis, operational system analysis, and Vehicle Operating Cost (VOC) analysis. The results of this study show that the 6 planned routes located in the North Badung Region have an average of 31,803 potential passengers per day with an average vehicle requirement of 73 fleets, an average circulation time of 67.132 minutes, an average annual BOK of IDR 217,910,721.20 per fleet, and an average BOK per kilometer of IDR 4,529.00. The South Badung Region has an average of 12,787 passengers per day with an average vehicle requirement of 22 fleets, an average circulation time of 48 minutes, an average annual BOK of Rp216,741,880.89 per fleet, and an average BOK per kilometer of Rp4,600.45 per fleet. Thus, it can be concluded that each route in North Badung and South Badung has high potential demand for transportation, given the large number of vehicles needed to serve potential passengers.